Incorporating spatial autocorrelation in rarefaction methods: Implications for ecologists and conservation biologists. (October 2016) - Bacaro, Giovanni; Altobelli, Alfredo; Cameletti, Michela; Ciccarelli, Daniela; Martellos, Stefano; Palmer, Michael W.; Ricotta, Carlo; Rocchini, Duccio; Scheiner, Samuel M.; Tordoni, Enrico; Chiarucci, Alessandro
Highlights: Classic rarefaction methods were shown to be susceptible to spatial autocorrelation. Spatially Explicit Rarefactions account for the spatial autocorrelation in community data. Including spatial autocorrelation into rarefactions change the way nature reserves are prioritized. Abstract: Recently, methods for constructing Spatially Explicit Rarefaction (SER) curves have been introduced in the scientific literature to describe the relation between the recorded species richness and sampling effort and taking into account for the spatial autocorrelation in the data. Despite these methodological advances, the use of SERs has not become routine and ecologists continue to use rarefaction methods that are not spatially explicit. Using two study cases from Italian vegetation surveys, we demonstrate that classic rarefaction methods that do not account for spatial structure can produce inaccurate results. Furthermore, our goal in this paper is to demonstrate how SERs can overcome the problem of spatial autocorrelation in the analysis of plant or animal communities. Our analyses demonstrate that using a spatially-explicit method for constructing rarefaction curves can substantially alter estimates of relative species richness. For both analyzed data sets, we found that the rank ordering of standardized species richness estimates was reversed between the two methods. We strongly advise the use of Spatially Explicit Rarefaction methods when analyzing biodiversity: the inclusion of spatial autocorrelation into rarefaction analyses can substantially alter conclusions and change the way we might prioritize or manage nature reserves.